Formation of Motor Skills in Athletes in Bullet Shooting at the Initial Stage of Training - Anatolii Lopatiev; Andrii Demichkovskyi (Journal of Learning Theory and Methodology, 2022)
The purpose of the study – to describe the peculiarities of the formation of motor skills in athletes in bullet shooting at the initial stage of training.